Geodemographic analysis of socioeconomic area disparities in tuberculosis incidence in Osaka City, Japan - Kaori Yamamoto; Shouhei Takeuchi; Tomoki Nakaya; Naoya Fujiwara; Junji Seto; Jun Komukai; Yuko Tsuda; Hideki Yoshida; Takayuki Wada (Scientific Reports)
Abstract Regional disparities in the incidence of tuberculosis (TB) pose several challenges to effective TB control. This study aimed to investigate such disparities in Osaka City, Japan, by analyzing the relationship between TB incidence and residents’ socioeconomic indicators. Using 42 indicators from the 2010 population census, the city was clustered into 15 social areas through a factor analysis, and TB incidence during 2012–2016 was compared across the areas in 4,852 cases. Two geographically adjacent areas (Area D and O) exhibited significantly higher TB rates, each with distinct social characteristics. Area D consisted of a high proportion of young, single individuals working in the service sector as well as foreigners. Area O included a high proportion of day laborers, secondary industry workers, and individuals with lower educational levels. TB occurred more frequently in foreign-born patients aged < 60 years, and it was detected during treatment for other diseases in Area D compared with other areas. However, a high proportion of retreated patients aged 40–79 years, with a shorter delay in TB detection, was observed in Area O. The variations in this study provide insights into the relationship between socioeconomic indicators and regional disparities in TB incidence in local settings.